A comprehensive framework for optimal day-ahead operational planning of self-healing smart distribution systems. (July 2018) - Hosseinnezhad, Vahid; Rafiee, Mansour; Ahmadian, Mohammad; Siano, Pierluigi
Highlights: A comprehensive framework for optimal operational planning of smart distribution systems. A management model control the self-sufficiency level of system. A self-healing strategy based on the island partitioning to restore maximum consumers. Metrics are integrated in the proposed island partitioning method. Abstract: Providing a cost-efficient and sustainable energy is one of the critical features in modern societies. In response to this demand, this paper proposes a comprehensive framework for optimal day-ahead operational planning of smart distribution systems considering both normal and emergency conditions. The proposed procedure for normal mode minimizes the operation costs and provides sustainability using the seamlessness index. By adjusting this index, the system can be adapted to achieve the desired self-sufficiency level along a specified planning horizon thanks to exploiting the sufficient local generations. The operational planning of emergency mode is integrated into the proposed framework to provide the optimal schemes which can handle the possible abnormal conditions using the available local generations and guarantee the desired resiliency level. In emergency mode, the proposed self-healing strategy will sectionalize the isolated area of the distribution system into island partitions to provide reliable power supply to the critical loads continuously. A set of key operational metrics including power loss, load priority, and system-related constraints are integrated into the proposed island partitioning procedure which promotes the functionality of the method. The proposed framework is implemented on a modified PG&E 69-bus distribution system and is investigated through different case studies. The results of case studies demonstrate significant improvements and benefits which are obtained by applying the proposed framework.